STRATEGIES OF THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION IN RECORDING MARRIAGE CERTIFICATES FOR THE CHINESE-INDONESIAN COMMUNITY IN SINGKAWANG, WEST KALIMANTAN PROVINCE - Femmy Febriyanti; Gatiningsih Gatiningsih; Fazri Ramadhan; Fitrah Alamsyah (Program Studi Studi Kependudukan dan Pencatatan Sipil, 2024)
Singkawang is a city home to a majority Chinese-Indonesian population with diverse cultural practices, one of which is the tradition of photo marriage (kawin foto). Within the Chinese-Indonesian community, this practice is often considered sufficient without formally registering the marriage with the Department of Population and Civil Registration. Consequently, the ownership rate of marriage certificates among the Chinese-Indonesian community in Singkawang remains low. This study aims to explore the strategies employed by the Department of Population and Civil Registration to address the low rate of marriage certificate ownership, focusing on the cultural practices and traditions of the Chinese-Indonesian community as objects of the study. The study employs a descriptive qualitative method with an inductive approach. Data were collected through observation, interviews, and documentation. The data analysis technique utilized is the ASOCA framework, which includes Ability, Strength, Opportunity, Culture, and Agility. The findings of this study indicate that 1) the Department of Population and Civil Registration has implemented strategies to encourage marriage registration, which include socialization among the Chinese-Indonesian community regarding marriage registration, building collaborations among institutions as well as vihara (Buddhist temples) or klenteng (Chinese temples), improving public services, providing foreign language training for staff, and offering mobile or on-the-spot services. 2) The challenges identified include: limited public knowledge about marriage registration, the absence of formalized written agreements, the inability of some vihara and klenteng to issue marriage blessing certificates, a shortage of civil servants (ASN) in the Department of Population and Civil Registration, the inactive status of the Dukcapil Online system, and insufficient foreign language skills among staff members. 3) To address these challenges, the Department of Population and Civil Registration has conducted socialization to the community and submitted requests for additional civil servants. Keywords: Marriage Certificate, ASOCA, Photo Marriage, Chinese-Indonesian Community, Registration, Strategy.